Lithium doped poly(3‑hexylthiophene) for efficient hole transporter and sensitizer in metal free quaterthiophene dye treated hybrid solar cells - Pirashanthan, A.; Dhayalan, V.; Robertson, N.; Ravirajan, P. (Scientific Reports, 2021)
This work focuses on the role of Lithium doped Poly(3-hexylthiophene)(P3HT) in metal-free quaterthiophene (4T) dye treated Titanium dioxide ( TiO2) based hybrid solar cells. The dye treated hybrid solar cells with Lithium doped P3HT showed efficiencies (3.95%) of nearly a factor of four times higher than the pristine P3HT based control TiO2/ 4T/P3HT devices (1.04%). The enhancement of the efficiency is mainly due to highly efficient charge collection attributed to enhanced charge transport and light harvesting properties of Lithium doped P3HT polymer. The optimized solar cells with Lithium doped P3HT showed a high short circuit current density over 13 mA/cm2, under simulated irradiation of intensity 100 mW/cm2 with AM 1.5 filter. This significant increase in current density in TiO2/ 4T/ doped P3HT solar cell is also confirmed by both the broadened External Quantum Efficiency spectrum and significant photoluminescence quenching upon replacement of pristine P3HT with doped P3HT on 4T dye treated TiO2 electrode. With Lithium doped Spiro-OMeTAD instead of Lithium doped P3HT, similar devices showed efficiencies over 3.30% under simulated irradiation of 100 mW/cm2 with AM 1.5 filter.